The issue of the persistent informal economy in Brezhnevian Stagnation exacerbated by the fact of the establishment of the “Little Deal”, - an extension of the “Big Deal” established in Stalin’s period - Smagulov, Tamyrlan (Nazarbayev University School of Sciences and Humanities, 2025)
The roots of informal economy in the stagnation period and its expansion in Soviet command economy is mostly attributed to Brezhnev's establishment of the “Little Deal”, which itself traces back its origin in Stalin’s “Big Deal”. Deal in the context of informal economy must be understood as thorough Soviet state policy and attitude to ignore and even rely on the informal economic activities through tacit agreement between state and citizens. Both of these “Deals” are inseparable and belong to the continual tradition of state’s blind eye attitude to certain economic activities motivated by most obvious economic challenges to meet the quotas of Five Year Plans by using or, better in our case, passive use of any necessary tool like informal economy to confront the shortages of command economy, and also motivated by state’s strategy to balance between the economic and political freedoms provided for the population.
Keywords: type of access: open access; informal economy